Insulin-induced enhancement of MCF-7 breast cancer cell response to 5-fluorouracil and cyclophosphamide - Siddarth Agrawal; Mateusz Łuc; Piotr Ziółkowski; Anil Kumar Agrawal; Ewa Pielka; Kinga Walaszek; Krzysztof Zduniak; Marta Woźniak (Tumor Biology)
The study was designed to evaluate the potential use of insulin for cancer-specific treatment. Insulin-induced sensitivity of MCF-7 breast cancer cells to chemotherapeutic agents 5-fluorouracil and cyclophosphamide was evaluated. To investigate and establish the possible mechanisms of this phenomenon, we assessed cell proliferation, induction of apoptosis, activation of apoptotic and autophagic pathways, expression of glucose transporters 1 and 3, formation of reactive oxygen species, and wound-healing assay. Additionally, we reviewed the literature regarding theuse of insulin in cancer-specific treatment. We found that insulin increases the cytotoxic effect of 5-fluorouracil and cyclophosphamide in vitro up to two-fold. The effect was linked to enhancement of apoptosis, activation of apoptotic and autophagic pathways, and overexpression of glucose transporters 1 and 3 as well as inhibition of cell proliferation and motility. We propose a model for insulin-induced sensitization process. Insulin acts as a sensitizer of cancer cells to cytotoxic therapy through various mechanisms opening a possibility for metronomic insulin-based treatments.